Image Guided Percutaneous Cholecystostomy–A Single Center Experience - Narayanan, Sathya; Keshava, Shyamkumar N.; Moses, Vinu; Ahmed, Munawwar; Padmanabhan, Aswin; Joseph, Philip (Journal of Clinical Interventional Radiology ISVIR, 2020)
Purpose To assess the technical feasibility of percutaneous cholecystostomy (PCC) for acute cholecystitis and formulate an algorithm for PCC.Materials and methods This is a retrospective study of 35 patients (28 male and 7 female; mean age 60 years) who underwent image-guided PCC from 2008 to 2018 at a tertiary care hospital in South India. Descriptive summary statistics and frequencies were used to assess the technical success and complications.Results The patients (35/35) presented with fever, abdominal pain, and a few of them had severe sepsis. All these patients were high risk for surgery considering the comorbidities (17/35) and hemodynamic instability (18/35). PCC was performed under ultrasoundguidance, through transhepatic approach, and using single puncture and modified single puncture techniques. The procedure was technically successful in all 35 patients (100%). Two patients (2/35) did not improve clinically after PCC; hence, they were taken up for emergency cholecystectomy with high-risk consent. One patient required a repeat procedure after 3 days due to tube dislodgement. There were no major procedure-related complications.Conclusion Image-guided PCC can be performed safely and is effective for treating high-risk patients with acute cholecystitis.
Keywords: percutaneous cholecystostomy; ultrasound guidance; single puncture technique